Pengaruh Pengelolaan Kelas Terhadap Hasil Belajar Matematika Siswa Kelas IV di SDN 42 Kota Bengkulu - Yolanda Maulidah; Victoria Karjiyati; Syahril Yusuf (JURIDIKDAS, 2019)
The purpose of this study is to determine the effect of classroom management on mathematics learning outcomes at class IV SDN 42 Kota Bengkulu. The type of this study was quantitative. The research method used was Quasi Experimental Design with the Matching Only Pretest-Posttest Control Group Design design, where the test taking was done before and after treatment. Subjects in this study were the fourth grade students of SDN 42 Kota Bengkulu consisting of IVC classes as experimental class and class IVB as the control class. The research instrument used was a multiple choice test given through pretest and posttest. The results showed that the t-test calculataion on pretest was (1.37) <t table (2.00) which means there was no average difference in the experimental class and control class, on the posttest t count (3.38) t table (2.00) which means there is an average difference in experiment and control class. The increase in pretest-posttest in the experimental class 64%, whereas in the control class pretest-posttest rise 59%. Of the increase in pretest-posttest showed that the increases in the experimental class was higher, it indicates that there was a classroom management influence on learning outcomes Mathematics Elementary School fourth grade students 42 Bengkulu City.